Experimental study on mechanical properties of corroded stainless-clad bimetallic steel bars. (14th June 2021) - Hua, Jianmin; Wang, Fei; Huang, Lepeng; Wang, Neng; Xue, Xuanyi
Highlights: Corrosion morphology of SCBSB with different corrosion degrees was studied. Adverse influence of corrosion on mechanical properties of SCBSB was quantified. Degradation coefficients of different kinds of steel bars were compared. Abstract: The mechanical properties of stainless-clad bimetallic steel bars (SCBSBs), which consist of S30408 stainless steel as the cladding metal and HRB400 carbon steel bars as the substrate, were experimentally investigated. The results of a tensile coupon test indicated a clear yield plateau in the stress–strain curve of the SCBSBs. The metallurgical bonding ensured stable composite working performance between the cladding layer and the substrate. Accelerated electrochemical corrosion was performed to obtain different corrosion degrees in the SCBSB specimens, and their mechanical properties were investigated. The corrosion performance of SCBSB specimens with different corrosion degrees was introduced. The experimental results indicated that an increase in the degree of corrosion resulted in a decrease in yield strength ( fy ), ultimate strength ( fu ), ultimate strain ( εu ) and elongation percentage ( δ ). The adverse effects of corrosion on the fy, fu and εu were quantified through the proposed linear formulae. A nonlinear formula was proposed to predict the relationship between the degree of corrosion and δ for the SCBSBs. Furthermore, a comparison between the SCBSBs, homogeneous carbon steel bars, and stainless steel bars with different corrosion degrees was conducted. Based on the minimum required values of fy, fu, and δ as per the GB/T 1499.2–2018 standard, the corrosion degrees of the SCBSB should be restricted to 13.9%, 14.6%, and 27.7%, respectively.